Impact of Air Pollution on Age and Gender Related Increase in Cough Reflex Sensitivity of Healthy Children in Slovakia - Demoulin-Alexikova, Silvia; Plevkova, Jana; Mazurova, Lenka; Zatko, Tomas; Alexik, Mikulas; Hanacek, Jan; Tatar, Milos (Frontiers in Physiology, 2016)
Background. Numerous studies show higher cough reflex sensitivity (CRS) and cough outcomes in children compared to adults and in females compared to males. Despite close link that exists between cough and environment the potential influence of environmental air pollution on age- and gender -related differences in cough has not been studied yet. Purpose. The purpose of our study was to analyse whether the effects of exposure to environmental tobacco smoke (ETS) from parental smoking and PM10 from living in urban area are implied in age- and gender-related differences in cough outcomes of healthy, non asthmatic children. Assessment of CRS using capsaicin and incidence of dry and wet cough was performed in 290 children (mean age 13.3±2.6 yrs (138 females/152 males). Results. CRS was significantly higher in girls exposed to ETS [22.3 μmol/l (9.8 – 50.2 μmol/l)] compared to not exposed girls [79.9 μmol/l (56.4 – 112.2 μmol/l), p=0.02] as well as compared to exposed boys [121.4 μmol/l (58.2 – 253.1 μmol/l), p=0.01]. Incidence of dry cough lasting more than 3 weeks was significantly higher in exposed compared to not exposed girls. CRS was significantly higher in school-aged girls living in urban area [22.0 μmol/l (10.6 – 45.6 μmol/l)] compared to school-aged girls living in rural area [215.9 μmol/l (87.3 – 533.4 μmol/l); p=0.003], as well as compared to teenage girls living in urban area [108.8 μmol/l (68.7 – 172.9 μmol/l); p=0.007]. No CRS differences were found between urban and rural boys when controlled for age group. No CRS differences were found between school-aged and teenage boys when controlled for living area. Conclusions. Our results have shown that the effect of ETS on CRS was gender specific, linked to female gender and the effect of PM10 on CRS was both gender and age specific, related to female gender and school-age. We suggest that age and gender related differences in incidence of cough and CRS might be, at least partially, ascribed to the effect of environmental pollutants. The role of age and gender in the effect of air pollution on cough strongly suggest some interplay of development with biological and behavioural factors.